Mer Blanche, Bouches de la Dvina du Nord, port d'Arkhangelsk / d'après la carte russe de 1928 , Service hydrographique de la marine . 1937 (1946)
Corr. . 1946 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange Grayscale; 1:70,000